HER2-directed antibodies, affibodies and nanobodies as drug-delivery vehicles in breast cancer with a specific focus on radioimmunotherapy and radioimmunoimaging - Altunay, Betül (Eur J Nucl Med Mol Imaging, 2020)
PURPOSE: The aim of the present paper is to review the role of HER2 antibodies, affibodies and nanobodies as vehicles for imaging and therapy approaches in breast cancer, including a detailed look at recent clinical data from antibody drug conjugates and nanobodies as well as affibodies that are currently under development. RESULTS: Clinical and preclinical studies have shown that the use of monoclonal antibodies in molecular imaging is impaired by slow blood clearance, associated with slow and low tumor uptake and with limited tumor penetration potential. Antibody fragments, such as nanobodies, on the other hand, can be radiolabelled with short-lived radioisotopes and provide high-contrast images within a few hours after injection, allowing early diagnosis and reduced radiation exposure of patients. Even in therapy, the small radioactively labeled nanobodies prove to be superior to radioactively labeled monoclonal antibodies due to their higher specificity and their ability to penetrate the tumor. CONCLUSION: While monoclonal antibodies are well established drug delivery vehicles, the current literature on molecular imaging supports the notion that antibody fragments, such as affibodies or nanobodies, might be superior in this approach.